Read under the shade: Schorge School in Burkina Faso and the Selva Plan in Peru - Cigarini Castelbarco, Tommaso (2022)
The present article speaks about the project of the Schorge school in Koudougou, Burkina Faso. It is an architecture built with limitations of all kinds: economic, infrastructural, climatic and social. The objective is to save the value of a building committed to the surrounding environment, the local culture and the population. It is proposed a parallel with the recent projects of Peruvians schools proposed by the Plan Selva. It is evaluated how Peru and Africa, although being two different realities, have common characteristics.